The role of coping strategies in alleviating the psychological pressures of football referees during quarantine - Zaoui , Abdelhalim (sports creativity, 2025)
This study aims to know the role of confrontational strategies in alleviating the psychological pressures of football referees during quarantine, as well as knowing the most used confrontational strategies by referees, and the study relied on the descriptive approach as it fits with the subject of the study, and the researcher used the confrontational strategies scale and was applied to A sample of 15 referees from the Professional League of Algeria.The results obtained after applying the appropriate statistical methods and by extrapolating the tables, analyzing and interpreting them, showed the following• -All hypotheses were fulfilled for the sample that we chose • - Referees tend to use problem-focused coping strategies first • Then confrontational strategies focused on social support and to a lesser degree emotional confrontational strategies